Activated char supported Fe-Ni catalyst for syngas production from catalytic gasification of pine wood. (November 2021) - Hu, Jianjun; Jia, Zhentao; Zhao, Shuheng; Wang, Wei; Zhang, Quanguo; Liu, Ronghou; Huang, Zhen
Graphical abstract: Highlights: Fe-Ni/AC exhibited excellent catalytic performance at low temperature (750°C). The steam could enhance the catalytic effect of Fe-Ni. Fe-Ni/AC had catalytic effect on the biomass gasification intermediates. Fe-Ni/AC exhibited catalytic activity during five times reuse without regeneration. Abstract: Char-based catalyst has a promising application for biomass thermal conversion technology. In this work, Fe-Ni/Activated Char (AC) catalyst was prepared by impregnation method and used for the catalytic gasification of pine wood to obtain syngas. Further, the catalytic performance of Fe-Ni/AC was established by doing a comparative study of catalytic gasification of different biomass feedstocks. The results showed that under the catalysis of Fe-Ni/AC, the increase of gasification temperature was beneficial to increase gas yield, but not conducive to regulate the H2 /CO ratio of syngas. The steam flow rate was directly related to the catalytic effect of Fe-Ni. The H2 /CO ratio of syngas could reach 1.97 under the optimal conditions. Fe-Ni/AC had different catalytic effects on different biomass feedstocks, with the best for pine wood and the worst for cotton stalk, indicating that gasification intermediates of pine wood were difficult to decompose and depended more on catalyst.